An in silico analysis of the glutamate dehydrogenases of Teladorsagia circumcincta and Haemonchus contortus - Simon Brown (University of Plovdiv, 2015)
View at Publisher Website:http://www.jbb.uni-plovdiv.bg/documents/27807/352484/jbb_2014-3%281%29-pages_49-60.pdf. This is an open-access journal distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives license (http://creativecommons.org/licenses/by-nc-nd/3.0/).